If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4z + 9 = 31 Reorder the terms: 3 + 9 + 4z = 31 Combine like terms: 3 + 9 = 12 12 + 4z = 31 Solving 12 + 4z = 31 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4z = 31 + -12 Combine like terms: 12 + -12 = 0 0 + 4z = 31 + -12 4z = 31 + -12 Combine like terms: 31 + -12 = 19 4z = 19 Divide each side by '4'. z = 4.75 Simplifying z = 4.75
| 8(y+6)=128 | | 3(2x-5)+4(x+2)=-7 | | x^5-2x^4-8x^3=0 | | 2(x+4)=38-4x | | 6v+32=-6+8(v+4) | | -5/8=g-1/4 | | 0.6x=28.3 | | -6(4n-6)-2n=-7n+17 | | y-4=6 | | h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x | | 4c+0=48 | | 3g-1+2g+8=g+2 | | A=5i+7j | | u+6=v | | -5+3x+3+2= | | -2(7-4)+4=-4 | | 7a=15a-80 | | 15y-12y=24 | | 0.02=100 | | 20y^7v^8u^2= | | 3(-2+x)=-24 | | 2b-6-3b-b= | | 10+7x=5x-6 | | (2x-1)(x+3)=(x-3)(x+1) | | 3x+21=68 | | -72-11c+6c^2=0 |